Theoretical study on the degradation mechanism of methamidophos and chloramine phosphorus with OH radicals. Issue 17 (4th June 2015) - Sun, Shengmin; Zhang, Kun; Lu, Yang; Liu, Ping; Zhang, Hui
<x xml:space="preserve">Abstract</x> Theoretical investigation on the gas‐phase degradation reaction mechanism of methamidophos (MAP) and chloramine phosphorus (CHP) with OH radicals is performed. The equilibrium geometries and the harmonic vibration frequencies of the stationary points are obtained at M06‐2x/6‐31+G(d, p) level, and the higher‐level energetic information is further refined at M06‐2x/6–311++G(3df, 2p) level. The rate constants for the 14 reaction channels are calculated by the improved canonical variational transition state theory with small‐curvature tunneling correction over the temperature range 200–2000 K. The three‐parameter expressions of k1(T) = 1.53 × 10−19T2.74exp(−1005.12/T), k2(T) = 1.36 × 10−20T3.02exp(−1259.56/T) are given. The total rate constants of all reaction channels of MAP with OH radicals are in good agreement with the available experimental data. Our results indicate that the H‐abstraction reactions on methyl are the major channels for the reaction of MAP and CHP with OH radicals. © 2015 Wiley Periodicals, Inc.